Reduction of copper ions release by a novel ecofriendly electropolymerized nanolayer obtained from a natural compound (carvacrol) - Bertuola, Marcos (2016)
The release of copper ions by copper-containing devices, equipments and facilities represents a potential risk for biological systems. Different inhibitory treatments (CuIT) that use organic compounds have been proposed to reduce this environmental hazard but many of them are not in accordance with new regulations. The development of an ecofriendly CuIT based on the use of carvacrol, a natural phenolic compound present in essential oils, is reported here. The effects of carvacrol adsorption (adCarv) and its electropolymerization (polyCarv) were examined. Electropolymerization was attained after cycling the copper electrode in the 0.3-1.0 V potential range. Electrochemical techniques complemented by ATR-FTIR, XPS, SEM and AFM surface analyses were used to evaluate the composition and characteristics of the layers. Results demonstrated that adCarv includes cetonic structures while polyCarv additionally contains ether bonds. AFM and SEM observations showed the presence of round nanoglobules, larger for adCarv (close to 50 nm diameter). Cytotoxicity of adCarv and polyCarv layers on copper was also evaluated. The comparative analysis of both treatments revealed that polyCarv nanolayer is highly protective while the adCarv layer is weakly protective and reduction in cell viability was found. It was concluded that CuIT that leads to polyCarv nanolayer is very effective and ecofriendly.